Levels and Exposure Risks of Lead, Arsenic and Mercury from Selected Lipstick and Nail Polish Cosmetics Marketed in Dar es Salaam, Tanzania - Kulwa, Gerald S.; Mihale, Matobola J (Tanzania Journal of Science, 2020)
Presence of Pb, As and Hg in selected lipstick and nail polish cosmetics sold at different shopping malls and retail outlets in Dar es Salaam was determined by microwave plasma atomic emission spectrometry due to their public health effects. Pb was detected in 100% (n = 25) of lipsticks and 53.3% (n = 15) of nail polishes. Arsenic was detected in 36% of lipsticks and 86.7% of nail polishes, and Hg was detected in 44% of lipsticks and 80% of nail polishes. All metal levels in both cosmetics were below the World Health Organisation (WHO) and Tanzania Bureau of Standards (TBS) maximum recommended limits. Health-based risks were evaluated using chronic daily intake (CDI), non-carcinogenic hazard quotient (HQ), hazard index (HI) as well as carcinogenic total risk. CDI values in all cosmetics were lower than maximum tolerable daily intake (MTDI). HQs of all metals in most of the lipsticks and all nail polishes were < 1, indicating little health risks. Both HI and carcinogenic risk were lower, indicating that they are relatively safe and have little potential carcinogenic risk. Determined potential carcinogenic risks were lower, indicating little carcinogenic risk. Awareness of potential effects and continuous monitoring are recommended to raise awareness of consumers and control quality of cosmetics as metals are cumulative toxicants.